Pneumococcus nasopharyngeal carriage in children attending an academic hospital in Pretoria, South Africa, after the introduction of pneumococcal vaccine - Charity Newton; Harry Maake; Caroline Maluleka; Siyazi Mda (Southern African Journal of Infectious Diseases, 2019)
Background: In 2009, pneumococcal conjugate vaccine was introduced in South Africa. However, there are concerns that this could lead to an increase in colonisation of non-vaccine serotypes (serotype replacement).